First person - Roberta Besio (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Roberta Besio is first author on 'Cellular stress due to impairment of collagen prolyl hydroxylation complex is rescued by the chaperone 4-phenylbutyrate', published in DMM. Roberta is a postdoc in the lab of Antonella Forlino at University of Pavia, Italy, investigating collagen and genetic diseases of the connective tissue.